Morphological change and the influence of language contacts in Estonian - Grünthal, Riho (2021)
Estonian is an illustrative example of a modern language that was intensively influenced by morphological attrition and foreign interfernce during the last millennium. The most salient typological differences of Estonian with respect to northern Finnic languages such as Finnish, Karelian and Veps are based on the loss of several important suffixes, in particular those of certain grammatical cases. This article discusses the interliaison of morphological and contact-induced change in the evidence of Estonian inflectional case system, case syncretism and certain adverbial constructions. The main hypothesis is that diachronic changes often do not happen independently of one another and endogenous and contact-induced changes in Estonian affect the same functional domains. The conclusions of this article are mainly based on language-specific analysis and most of the data is drawn from Estonian. Nevertheless, there are certain parallels between case syncretism in Estonian, Vote and South-West Finnish dialects that will be used for comparative evidence. Convergent changes suggest that a particular morphological change does not inevitably have identical consequences even in genetically closely related languages.numbered, too, please let me know. Peer reviewed